Pendampingan Dan Penerapan Dalam Penyusun Laporan Keuangan Berdasarkan SAK EMKM Pada UMKM - Yunarti Elisabeth Sunaryo; Endang Sri utami (Jurnal Kabar Masyarakat, 2023)
This service aims to help prepare financial reports based on the Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) at Pet Shop Bisopo Candi and Pet Shop Bisopo Kalasan. The research method used is quantitative descriptive. The information obtained is in the form of income and expenditure record documents available for the two MSMEs that have been recorded. Both MSMEs have not been able to prepare financial reports in accordance with SAK EMKM because they do not have an economic background. MSMEs only make daily sales reports and inventory entry reports manually. The aim of this service is to assist MSMEs in preparing financial reports in accordance with SAK EMKM. These two businesses are a group of micro MSMEs. These 2 businesses operate in the field of animal care, animal feed and accessories. In this service, the author carried out previous training methods and provided assistance in preparing financial reports. The author conducted interviews and counseling. The results of this service are in the form of financial reports that have been prepared in accordance with SAK EMKM.